Hydrogen storage using a hot pressure swing reactor - Jorschick, Holger; Preuster, Patrick; Dürr, Stefan; Seidel, Alexander; Müller, Karsten; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2017)
Our contribution demonstrates that hydrogen storage in stationary Liquid Organic Hydrogen Carrier (LOHC) systems becomes much simpler and significantly more efficient if both, the LOHC hydrogenation and the LOHC dehydrogenation reaction are carried out in the same reactor using the same catalyst. The finding that the typical dehydrogenation catalyst for hydrogen release from perhydro dibenzyltoluene (H18-DBT), Pt on alumina, turns into a highly active and very selective dibenzyltoluene hydrogenation catalyst at temperatures above 220 °C paves the way for our new hydrogen storage concept. Herein, hydrogenation of H0-DBT and dehydrogenation of H18-DBT is carried out at the same elevated temperature between 290 and 310 °C with hydrogen pressure being the only variable for shifting the equilibrium between hydrogen loading and release. We demonstrate that the heat of hydrogenation can be provided at a temperature level suitable for effective dehydrogenation catalysis. Combined with a heat storage device of appropriate capacity or a high pressure steam system, this heat could be used for dehydrogenation.

Macrokinetic effects in perhydro-N-ethylcarbazole dehydrogenation and H2 productivity optimization by using egg-shell catalysts - Peters, Willi; Seidel, Alexander; Herzog, Stefan; Bösmann, Andreas; Schwieger, Wilhelm; Wasserscheid, Peter (Energy and Environmental Science, 2015)
This contribution deals with pore diffusion influences on the dehydrogenation kinetics of perhydro-N-ethylcarbazole (H12-NEC). The reaction is of high interest in the context of hydrogen storage in the N-ethylcarbazole (NEC)/perhydro-N-ethylcarbazole (H12-NEC) Liquid Organic Hydrogen Carrier (LOHC) system. The hydrogen content of H12-NEC is 5.8 wt% and total dehydrogenation releases for each mL of H12-NEC more than 600 mL of H-2. Further optimization of H12-NEC dehydrogenation catalysis requires a better understanding of the role of mass transfer effects. Pore diffusion effects have been studied by preparing egg-shell catalysts (Pt/gamma-alumina layer on alpha-alumina core) of different active layer thicknesses (24 -88 mu m). It has been found that even at very thin catalyst layers (24 mu m) the kinetic regime is limited to 235 degrees C, thus pore diffusion effects the dehydrogenation in almost all commercial catalysts strongly.